FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KECEMASAN IBU HAMIL TRIMESTER III MENGHADAPI PERSALINAN DI PUSKESMAS JATIROTO - Amelia, Rizkika; Winarni, Winarni (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
The condition of a mother's pregnancy can be influenced by physical, psychological, environmental, socio-cultural and economic factors. Psychological conditions related to pregnancy are anxiety. During the third trimester of pregnancy, most pregnant women experience real anxiety. In internal stressors, pregnant women's anxiety is influenced by the pregnant woman's internal psychological state, including age and gravida, while external stressors are found in her husband's support. Objective: To determine the factors associated with third trimester pregnant women's anxiety about giving birth at the Jatiroto Community Health Center. Method: This research uses quantitative data with an analytical observational research design using a cross sectional approach. Samples were taken using the consecutive sampling method as many as 44 samples of pregnant women in the third trimester. Results: The results of the study using the regression logistic test in multivariate analysis obtained a significant value of 0.001 < P. value 0.005. Conclusion: There is a relationship between husband's support and third trimester pregnant women's anxiety about giving birth at the Jatiroto Community Health Center.